Chain linking over December and methodological changes in the HICP: View from a central bank perspective - Andreas Dietrich; Martin Eiglsperger; Jens Mehrhoff; Elisabeth Wieland (European Central Bank (ECB), 2021)
Consumer price inflation, as measured by the year-on-year increase in the Harmonised Index of Consumer Prices (HICP), is used by the European Central Bank (ECB) for assessing its monetary policy. The European Statistical System regularly introduces methodological improvements into this chain-linked price index in the linking month (December). If the outcome of such changes is a new series with a very different profile in December - either due to changed seasonality or one-off (sampling) effects - significant statistical distortions may arise when the new index series is chain-linked to the existing series. This paper explains the mechanism behind statistical distortions due to chain linking and provides some recent examples from European price statistics. Several alternative chain-linking practices, as well as recommendations for data users on how to deal with such statistical breaks in the HICP, are presented.
Keywords: C43; E31; 330; Consumer prices; chain linking; index aggregation methods; seasonality; central bank communication